Enhancement of the tour guide webpage for Kinta tour guide webpage based on human computer interaction (HCI) elements by Jacob Nielsen - Lay Kee, New (2012)
Webpages are the pages which are available online and this is the site where Internet users can get a wide range of information from.Webpages can be divided into various types such as advertisements,articles, guidelines and so on. Webpage for tour guide is one of the significant and useful pages available online.Different types of webpages have different goals and information.However,there are many existing webpages that require enhancement to be more convenience,informative and attractive to the Internet users.This project is done in order to enhance the tourism webpage of Kinta Tour Guide Webpage. The Heuristic Usability rules of Human Computer Interaction (HCI) are utilized for the Kinta Tour Guide webpage enhancement.The effectiveness of the project is verified by bringing out random survey with questionnaire.It is the Research Methodology process. Then,it has been identified that the Kinta Tour Guide webpage is lack of information,creativity and so on.The existing system of the webpage has been surveyed by 30 respondents and their comments from the questionnaire are considered seriously to be applied in order to enhance the webpage based on the Heuristic Rules.Most of the respondents are unsatisfied with the unattractive design and boring contents of the existing system.There are three main Heuristic Usability Rules available which include 8 Golden Rules,Norman’s Principle and the Jacob Nielsen’s Rules.In the project of Enhancement of the Tour Guide Webpage for Kinta Tour Guide Webpage Based on Human Computer Interaction (HCI) Elements by Jacob Nielsen,the most suitable rule to be applied is the Jacob Nielsen’s Heuristic Rules.Hence with the suitable Heuristic rules and useful comments from the survey,the enhanced webpage can fulfil all of the requirements from the viewers.